Regulation, innovation, and the introduction of new telecommunications services - James E. Prieger (University of California, Department of Economics, 2000)
I examine the effects of FCC regulation on the innovation and introduction of advanced telecommunications services in the U.S. An interim of lighter regulation provides an experiment to test the regulatory regime''s impact on innovation. The econometric model comprises an arrival process (for service innovation) followed by a duration process (for regulatory delay). The number of services the firms created created during the interim is 60-99% higher than the model predicts they would have if the stricter regulation had still been in place. Overall, firms would have introduced 62% more services to consumers during the study period if the regulation had not been in place.
Keywords: L51; L96; 330; Telekommunikation; Regulierung; Innovation; Schätzung; USA